As tradições das Congadas da Comunidade Negra dos Arturos em A Árvore dos Arturos & outros poemas, de Edimilson de Almeida Pereira - Manoela Fernanda Silva de Matos (2023)
This work aims to analyze the aesthetic-literary plurality of Edimilson de Almeida Pereira. This required going through literary historiography and the place occupied by black literature within Brazilian literature. Therefore, it was necessary to read several researchers who deal with black writing, such as Eduardo de Assis Duarte, Benedita Damasceno, Nazareth Fonseca, and others. The plurality of Almeida Pereira's writing can be seen when we portray his two faces: researcher on the one side and writer on the other, seeking congruence between the two personas. He is, therefore, one of the great names in contemporary literature. As a researcher, he devoted himself to studying popular manifestations, especially those of African origin, and during one of these field studies, he met the Black Community of Arturos, located in Minas Gerais. Based on this contact, Almeida Pereira, in partnership with Núbia Gomes Pereira, wrote the book Negras raízes mineiras: os Arturos (Black roots of Minas Gerais: the Arturos), published in 1988 and republished in 2000. Concomitantly with this publication, Edimilson de Almeida Pereira published the poetic work A Árvore dos Arturos & outros poemas ("The Arturos Tree & Other Poems," 1988). This collection includes the poem A Árvore dos Arturos ("The Arturos Tree"), which will be analyzed in this paper to prove the importance of the Congadas in maintaining the Black Community of Arturos, thus becoming the expression of a people as a way of being and living that reaffirms the identity of the Arturos, both individually and collectively. Understanding this organizational system of the Arturos required us to read studies of researchers dealing with Congadas, such as Glaura Lucas, Leda Martins, Edimilson de Almeida Pereira, Núbia Gomes Pereira, and others, who will serve as a theoretical contribution to this research. In this way, it became evident that the perpetuation of the Arturos in the figure of Arthur Camilo, in which his memory reverberates in his descendants, in the experiences and experiments of the Community, and, above all, in the rites and precepts of the Congada that transcend the tenuous line between heaven and earth, myth and reality, is how the Black Community of the Arturos was formed; this is how the Arturos are. Keywords: Edimilson de Almeida Pereira; Congadas; Black literature; Popular traditions.